The C-terminal Domain (CTD) of Human DNA Glycosylase NEIL1 Is Required for Forming BERosome Repair Complex with DNA Replication Proteins at the Replicating Genome - Pavana M. Hegde; Arijit Dutta; Shiladitya Sengupta; Joy Mitra; Sanjay Adhikari; Alan E. Tomkinson; Guo‐Min Li; István Boldogh; Tapas K. Hazra; Sankar Mitra; Muralidhar L. Hegde (2015)
The human DNA glycosylase NEIL1 was recently demonstrated to initiate prereplicative base excision repair (BER) of oxidized bases in the replicating genome, thus preventing mutagenic replication. A significant fraction of NEIL1 in cells is present in large cellular complexes containing DNA replication and other repair proteins, as shown by gel filtration. However, how the interaction of NEIL1 affects its recruitment to the replication site for prereplicative repair was not investigated. Here, we show that NEIL1 binarily interacts with the proliferating cell nuclear antigen clamp loader replication factor C, DNA polymerase δ, and DNA ligase I in the absence of DNA via its non-conserved C-terminal domain (CTD); replication factor C interaction results in ∼8-fold stimulation of NEIL1 activity. Disruption of NEIL1 interactions within the BERosome complex, as observed for a NEIL1 deletion mutant (N311) lacking the CTD, not only inhibits complete BER in vitro but also prevents its chromatin association and reduced recruitment at replication foci in S phase cells. This suggests that the interaction of NEIL1 with replication and other BER proteins is required for efficient repair of the replicating genome. Consistently, the CTD polypeptide acts as a dominant negative inhibitor during in vitro repair, and its ectopic expression sensitizes human cells to reactive oxygen species. We conclude that multiple interactions among BER proteins lead to large complexes, which are critical for efficient BER in mammalian cells, and the CTD interaction could be targeted for enhancing drug/radiation sensitivity of tumor cells.